2017
DOI: 10.1007/s12350-016-0682-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of serial FDG PET for assessing therapeutic response in patients with cardiac sarcoidosis

Abstract: Our results indicated that serial FDG PET is feasible to determine the extent of disease activity and to quantitatively assess the response of cardiac sarcoidosis to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…pejorative factor [11, 21-23, 25, 30, 37-39]. Interestingly, repeat FDG PET scan may help to determine the extent of disease activity and to assess the cardiac response to therapy [40][41][42].…”
Section: Plos Onementioning
confidence: 99%
“…pejorative factor [11, 21-23, 25, 30, 37-39]. Interestingly, repeat FDG PET scan may help to determine the extent of disease activity and to assess the cardiac response to therapy [40][41][42].…”
Section: Plos Onementioning
confidence: 99%
“…In fact, a re-review of CMR in the above cases found that the scan in Case 1 was indeterminate rather than a true negative due inadequate nulling of the myocardium in the delayed enhancement series. The resolution of FDG-PET avidity on serial imaging seen with the cases above is reassuring, especially given recent data demonstrating improved PET parameters correlate with improved LVEF and other clinical outcome measures [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 92%
“…18 F‐FDG PET is a useful modality to evaluate disease severity and activity in patients with CS . Moreover, previous reports showed serial 18 F‐FDG PET scanning was useful for evaluating therapeutic response and effect, believed to be associated with active inflammation . However, the usefulness of serial 18 F‐FDG PET scans for the diagnosis of isolated CS remains unknown.…”
Section: Discussionmentioning
confidence: 99%